Against Purity - Jonathan Barker (Ergo, An Open Access Journal of Philosophy)
A fundamental fact is “pure” just in case it has no grounded entities—ex. Tokyo, President Biden, the River Nile, Socrates, etc.—among its constituents. Purity is the thesis that every fundamental fact is pure. I argue that Purity is false. My argument begins with a familiar conditional: if Purity is true, then there are no fundamental “grounding facts” or facts about what grounds what. This conditional is accepted by virtually all of Purity’s defenders. However, I argue that it is also the first step toward Purity’s undoing. For, if every grounding fact has a ground, then some grounded entities have “groundmates” or distinct grounded entities that share their full grounds. But, if there are groundmates, then Purity is false. So Purity leads to a contradiction. Therefore, it is false. I close by noting that my argument against Purity also gives us a powerful reason to think that some grounding facts are fundamental.